SHARIA MARKETING : AKTIVITAS STRATEGIS UNTUK TUJUAN KESEJAHTERAAN MATERI DAN SPRITUAL - RUSTAM RUSTAM (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". Islamic marketing is operationally defined throughout the process of strategic activities undertaken by individuals and institutions in a lawful way to create, communicate and offer (products and services) for the purpose of material welfare and spiritual stakeholders based on the rules of the Qur'an and sunna both in the world until the end. There are several series of sharia marketing activities that are of concern. First, product creation. Explicitly in the creation or creation of products in sharia marketing must comply with halal terms, does not cause dirty or corrupt thoughts, does not interfere, does not contain elements of usury and maysir, morals, products in legal possession, the product must be submitted clearly and must be precise in quantity and quality. Second, the offer. The process of communication in sharia marketing is allowed to use both print and online media directly or indirectly while not contrary to the values of Islamic law. A communication effort in sharia marketing is recommended is communications that really exist so as not to cause any treatment of vanity. Third, the change of value (value). The process of change in value in the shariah marketing is not only orientation on changes in material values but changes in value by considering the spiritual values.